O fechamento dos cinemas em Ponta Grossa: particularidades de um processo histórico-cultural - Silva Junior, Nelson (2008)
The present work aims for knowing the processes of closure the cinemas in the city of Ponta Grossa (PR), relating to its social history context, in a period extending from the end of the 80’s, when it initiated the process of closure, until the beginning of the year 2000, when it opened the first rooms of movie exhibition located in a shopping mall. The very first hypothesis raised in this research was that the cinema represented a symbol of modernism and progress; the closure of these cinemas is highly related to a process of cultural stagnation and this closure had consequences to other sectors, such as the political, social and economic. In order to do so, the cinema was related to the everyday life, the identity, the culture and the memory, taking from the construction of different meanings of the cinema from eight people that had the cinema as an important reference back in those days. What’s the representation of the cinema to those people that took part through its rise and fall; in which way the cinemas of the city contributed to a construction of a collective identity and what is the relation between the cinemas of Ponta Grossa and the image of the city, those were important questions for the research. In order to understand the role of the cinemas and the reflex of its closure, we appeal to the following authors Marilena Chauí, Gutiérrez Alea, Agnes Heller, Michael Pollak, Beatriz Sarlo, John B. Thompson, and others, the conceptual guidelines of the present work.